2013
DOI: 10.2522/ptj.20130053
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Neuroplasticity for Motor Rehabilitation After Stroke: Considering the Effects of Aerobic Exercise and Genetic Variation on Brain-Derived Neurotrophic Factor

Abstract: Recovery of motor function after stroke involves relearning motor skills and is mediated by neuroplasticity. Recent research has focused on developing rehabilitation strategies that facilitate such neuroplasticity to maximize functional outcome poststroke. Although many molecular signaling pathways are involved, brain-derived neurotrophic factor (BDNF) has emerged as a key facilitator of neuroplasticity involved in motor learning and rehabilitation after stroke. Thus, rehabilitation strategies that optimize BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
239
1
30

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(275 citation statements)
references
References 66 publications
5
239
1
30
Order By: Relevance
“…23 Individuals' genetic profiles may also influence recovery. [24][25][26] While interest has centred on genes known to contribute to neuroplasticity, 27 there are a number of candidate biomarkers to consider as well as gene-gene interactions and epigenetics.…”
Section: Theme 2: Recovery Biomarkersmentioning
confidence: 99%
“…23 Individuals' genetic profiles may also influence recovery. [24][25][26] While interest has centred on genes known to contribute to neuroplasticity, 27 there are a number of candidate biomarkers to consider as well as gene-gene interactions and epigenetics.…”
Section: Theme 2: Recovery Biomarkersmentioning
confidence: 99%
“…It is well accepted that motor recovery after stroke is achieved through cortical reorganization, in which the brain and central nervous system (CNS) adapt in response to environmental and behavioral change to acquire novel information by modifying neural connectivity and function (Knaepen, Goekint, Heyman, & Meeusen, 2010;Mang, Campbell, Ross, & Boyd, 2013). Although the exact mechanism for cortical reorganization is not known, neurotrophins are thought to play a major role by enabling neuronal survival, potentiation, and differentiation; promoting dendritic growth and remodeling; and promoting synaptic plasticity (Lin & Kuo, 2013;Voss, Nagamatsu, Liu-Ambrose, & Kramer, 2011).…”
mentioning
confidence: 99%
“…The activity-dependent changes in the CNS and elevation of BDNF levels after acute bouts of aerobic exercise provide a theoretical rationale for exploiting the potential neurophysiologic effects of aerobic exercise as a means to promote motor recovery after stroke (Mang et al, 2013). Therefore, we developed a model to integrate aerobic exercise with task practice in an attempt to optimize motor recovery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not known whether the conventional gait training widely used in clinical physical therapy practice is able to induce changes in serum levels of brain-derived neurotrophic factor (BDNF), which could positively influence neurophysiological mechanisms. Studies have shown that acute and chronic exercises increase peripheral levels of BDNF, mainly after performing aerobic exercise [12][13][14][15][16]. Additionally, BDNF levels in the central nervous system are positively associated with peripheral BDNF levels, particularly serum and plasma, and therefore, circulating peripheral BDNF level has been suggested as a good biomarker for concentration brain this neurotrophin [17].…”
Section: Introductionmentioning
confidence: 99%